Analisis Kendala dalam Penggunaan Website Berbasis Artificial Intelligence (AI) sebagai Alat Bantu dalam Mengerjakan Tugas Akademik pada Mahasiswa Pendidikan Agama Islam Universitas Negeri Padang - Alfurqon, Muhamad Hadli; Wirdati, Wirdati (Lembaga Yasin AlSys, 2024)
This study explores the challenges faced by Islamic Education students at Universitas Negeri Padang in using AI-based websites to complete academic assignments. Using a qualitative method with a case study approach, data was collected through interviews, observations, and documentation, then analyzed to ensure validity. The findings indicate that websites such as ChatGPT, Perplexity, and Gemini.ai are used to answer academic questions, find scientific references, and analyze images and texts. However, challenges such as AI's limited understanding of religious studies, dependence on technology, and information reliability remain significant obstacles. Students use AI for structured assignments by obtaining topic explanations and scientific references, as well as for independent tasks such as studying lecture materials, creating presentations, translating languages, and answering discussion questions. While AI use has proven beneficial, the existing challenges need to be addressed to maximize its potential.